Floriculture enterprise: Blooming the flower of life - Kharga, Basu Deo; Roy, Rakesh (Indian Horticulture, 2022)
This is a success story of a professional driver who transformed himself into a successful entrepreneur in floriculture. Arun Chhetri (45 years old) having middle school level of education was residing in a small village of Kalimpong district, West Bengal. Horticulture always has a scope in the hills and particularly floricultureis gaining popularity among rural youth in the region. The economic analysis of last 5 years shows that the B:C ratio of enterprise was 3.33 annually and annual net income from the enterprise was `2.27 lakhs from a small piece of land of 35 decimal. Further, he has reported, if marketing channels were well established then the income can be enhanced many fold.